2018
DOI: 10.3390/mi9080397
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Microfluidic Technology for Cancer Applications and Liquid Biopsy

Abstract: There is growing awareness for the need of early diagnostic tools to aid in point-of-care testing in cancer. Tumor biopsy remains the conventional means in which to sample a tumor and often presents with challenges and associated risks. Therefore, alternative sources of tumor biomarkers is needed. Liquid biopsy has gained attention due to its non-invasive sampling of tumor tissue and ability to serially assess disease via a simple blood draw over the course of treatment. Among the leading technologies developi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 118 publications
0
30
0
Order By: Relevance
“…One such approach is to use label-free selection with specific protein markers to select or to deplete those cells that express a particular marker. 47,81 Other approaches to CTC isolation rely on differences in their physical property and use techniques, such as filtration, chip technology, density gradient centrifugation, electric field, sound waves 82 and microfluidic technology. 54,[83][84][85] Characterisation of CTCs can be performed by using immunocytochemistry, molecular technologies and/or functional assays.…”
Section: Circulating Tumour Cells Ctcs and Metastasismentioning
confidence: 99%
“…One such approach is to use label-free selection with specific protein markers to select or to deplete those cells that express a particular marker. 47,81 Other approaches to CTC isolation rely on differences in their physical property and use techniques, such as filtration, chip technology, density gradient centrifugation, electric field, sound waves 82 and microfluidic technology. 54,[83][84][85] Characterisation of CTCs can be performed by using immunocytochemistry, molecular technologies and/or functional assays.…”
Section: Circulating Tumour Cells Ctcs and Metastasismentioning
confidence: 99%
“…These platforms have grown in popularity due to their ability to automate laboratory functions and to integrate several laboratory functions onto a single chip. 8,31,43,74 Through innovations in micro-and nano-scale technology, these FIGURE 2. Structure and biomarkers of SARS-CoV-2 Virus.…”
Section: Lab-on-chip Biosensorsmentioning
confidence: 99%
“…Microfluidic devices focused on CTCs analysis include cellular segregation and examination, demonstrating high efficiency, reactivity and selectivity; low sample amount and reagent costs; and high liquid control capacity [32]. Most of the studies showed the development of microfluidic chips for CTCs capture using the affinity towards a specific cell membrane protein called "Epithelial Cell Adhesion Molecule" (EpCAM) [33]. This capture is achieved by the immobilization in the channels of the microfluidic system of specific antibodies against this EpCAM protein.…”
Section: Platforms Based On Circulating Tumor Cells Analysismentioning
confidence: 99%